Not-So-Magical Realism : A Climate Stress Test of the Colombian Banking System - World Bank (World Bank, Washington, DC, 2021)
This report identifies and assesses relevant physical and transition risks with focus on the banking sector. Banks constitute the largest segment of the Colombian financial sector with asset holdings of Colombian peso (Col dollars) 720 trillion (US209 billion dollars or 78 percent of gross domestic product [GDP]) in 2020. This includes both foreign and domestic banks. Some banks are parts of larger conglomerates in which the related entities could be exposed to similar climate-related financial risks, such as foreign banks, insurance companies, and asset managers. Insurance companies and asset managers are, however, not part of this report. The scope of our analysis includes both physical risks (that is, those emanating from weather-related events and gradual changes in climatic conditions) and transition risks (that is, those emanating from decarbonization of the global economy in line with targets in the Paris Agreement). The authors note that we use a broad definition of physical risks, covering both climate-related disaster risks and the effects of climate change on their probability distribution. In the remainder of the report, authors refer to the collection of these risks as climate-related financial risks, or climate-related risks in short. The report also builds on quantitative data from a range of sources to explore the vulnerability of banks in specific scenarios. The report bases its analysis on data provided by the SFC, the Central Bank of Colombia (BR), the National Planning Department (DNP), and the Institute of Hydrology, Meteorology and Environmental Studies (IDEAM), and further desk research. In general, the report focuses on three main channels through which climate-related risks affect Colombian banks’ balance sheet: the effects on credit risk in the loan portfolio, the effects on the market value of government bonds, and the effects on exposures through investments in other financial institutions. These three channels represent the most important asset classes, covering 79 percent of total assets in the Colombian banking sector. However, in some of our quantitative assessments, we limit our scope further owing to data limitations, including investments in related entities and noncorporate loans (the latter only for transition risk). Because data are not available for all potential channels that affect the financial sector, our outcomes can be conservative and lead to an underestimation of the total effect of climate risks on banks.